Alzheimer Patient Tracking System in Indoor Wireless Environment - Kristalina, Prima; Imanuddin, Achmad Ilham; Yuliana, Mike; Pratiarso, Aries; Astawa, I Gede Puja (European Scientific Journal, ESJ, 2017)
Alzheimer’s disease is a disease of the nerves that are irreversible, resulting in memory impairment. This condition resulted in Alzheimer’s patients easily lost because they forget the existence. In this research, we designed a tracking system for Alzheimer’s patients in a hospital environment, incorporating Kalman method to estimate the position of the patient. As known Received Signal Strength Indicator value is strongly influenced by environmental conditions that lead to the acquisition of position estimation is inaccurate. From the test results showed that the optimal Kalman estimated value obtained when the value of R = 0:01 and Q = 0.1 with the average percentage of error only 7.01 % of the actual patient position. The test results with various data variations also indicate the reliability of the Kalman method, because of the average estimated position approach the actual patient position.